Towards the Estimation of Canadian Wetland Methane Fluxes with Airborne Lidar - Kiemle, Christoph; Fruck, Christian; Fix, Andreas; Ehret, Gerhard; Quatrevalet, Mathieu (2024)
Airborne and satellite based lidar remote sensing combines the advantages of high measurement accuracy, large-area coverage and low-ambient-light measurement capability. The Merlin airborne demonstrator CHARM-F is an Integrated-Path Differential-Absorption (IPDA) lidar providing vertical column concentrations of carbon dioxide and methane up to the flight altitude along the flight track. It operated onboard the German HALO (high-altitude long-range) research aircraft during the CoMet 2.0 Arctic campaign in August and September 2022 over natural and anthropogenic sources of CO2 and CH4 in Canada. Natural methane fluxes from wetlands generally produce weak atmospheric concentration enhancements of the measured atmospheric column (<1%). To address this challenge, we initially use methane profiles from CAMS (Copernicus Atmosphere Monitoring Service) reanalyses to discard cases where long-range transport of methane within the free troposphere causes large gradients over the measurement area. We then use in-situ measurements of the Jena Instrument for Greenhouse gases (JIG) operating onboard the same aircraft to identify methane enhancements above wetlands during low-level flight segments within the boundary layer. Correlation analyses with lidar-detected enhancements above the same wetlands allow us to characterize the lidar detection limit. Aircraft in-situ wind measurements in the boundary layer provide plume drift and dilution information necessary for lidar-informed methane emission flux estimations using either the integrated mass enhancement (IME) approach or an upwind-downwind gradient analysis. Comparisons of the in-situ wind measurements with the CAMS wind fields reveal how well the fluxes can be assessed from solely remote sensing methane and model wind data in the absence of in-situ measurements. Measurement examples and preliminary results will be shown.